Legal Responsibility of the Trade Office for Defaulting on Contract Workers in the Construction of the Dakopamean People's Market (Study of Decision Number 7/Pdt.G/2022/PN Tli) - Sianturi, Andre Ferdy; Simamora, Janpatar; Siregar, Ria Juliana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This writing aims to delve into the legal responsibility in breach of contract disputes. Breach of contract refers to the inability of an individual or a party to fulfill obligations based on a prior agreement. In a breach of contract case, legal responsibility is an obligation imposed on a party as a form of accountability for the violation committed. This study also focuses on the basis of assessment used by law enforcers, namely the panel of judges, in deciding a breach of contract dispute involving the Department of Trade, which failed to fulfill its obligations to a contract worker in the construction of the Dakopamean Public Market, based on Decision Number 7/Pdt.G/2022/PN Tli, and the form of legal responsibility of the Department of Trade for the breach of contract in the construction project of the Dakopamean Public Market. This writing also emphasizes a normative legal research method of a descriptive nature, in which the results of the study will further examine the judges’ considerations in deciding a case, particularly in breach of contract matters.